Conditional Ablation of the Neural Cell Adhesion Molecule Reduces Precision of Spatial Learning, Long-Term Potentiation, and Depression in the CA1 Subfield of Mouse Hippocampus - Bukalo, O. (2014)
10.1523/JNEUROSCI.3298-03.2004